2004
DOI: 10.1017/s1041610204000420
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and appropriateness of psychotropic drug use in old age: results from the Berlin Aging Study (BASE)

Abstract: Background: The aim of this epidemiological study is to examine the prevalence and correlates of psychotropic drug use in the very old and to evaluate the appropriateness of psychotropic drug use in very old age.Methods: Data from the Berlin Aging Study (BASE), a multidisciplinary study of an age- and gender-stratified, randomly selected sample of elderly people living in Berlin are presented. Over-sampling, especially very old men, allows for powerful analyses of this population. All participants went through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
1
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(43 citation statements)
references
References 29 publications
3
36
1
3
Order By: Relevance
“…In our study, the prevalence of psychotropic drug use was found to be 13.8%, a value lower than the one found among elderly people living in higher income countries 3,[6][7][8][9] , and slightly higher than the one observed among Brazilian elderly in previous research 16 . Such differences between studies may have arisen due to issues related to the morbidity profile of studied populations and prescription patterns, which change according to context and time of conduction of studies.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…In our study, the prevalence of psychotropic drug use was found to be 13.8%, a value lower than the one found among elderly people living in higher income countries 3,[6][7][8][9] , and slightly higher than the one observed among Brazilian elderly in previous research 16 . Such differences between studies may have arisen due to issues related to the morbidity profile of studied populations and prescription patterns, which change according to context and time of conduction of studies.…”
Section: Discussioncontrasting
confidence: 82%
“…This result is not surprising, and is often mentioned in the literature in different scenarios 6,7,9,10,16 . Depression and sleep disorders are highly correlated 10 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The proposal is based on Swedish recommendations, internationally published explicit criteria and expert opinions. This indicator has been used in several research studies [9,[18][19][20][21][22][23] as well as in recent national assessments of quality and efficiency in the Swedish healthcare system [24]. The indicator is considered to be a proxy for polypharmacy (concurrent use of multiple drugs) and to signal poor quality in the treatment of psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Grande parte das idosas entrevistadas não soube informar desde quando utiliza benzodiazepínicos, informação esta que também não foi encontrada nos prontuários médicos. Esta limitação também foi encontrada por Linden et al 31 em um estudo sobre a prevalência do uso de benzodiazepínicos, em que as participantes não conseguiram dar informações mais consistentes sobre essa prática.…”
Section: Lazer N (T = 123) %unclassified